Detection of virulence genes in Malaysian Shigella species by multiplex PCR assay - Thong, Kwai Lin; Hoe, S.L.L.; Puthucheary, S.D.; Yasin, R.M. (BMC, 2005)
The mPCR system is reproducible, sensitive and is able to identify pathogenic strains of shigellae irrespective of the locality of the virulence genes. It can be easily performed with a high throughput to give a presumptive identification of the causal pathogen.